THE ARTS THEATRE, UNIVERSITY OF IBADAN, 1955-1985: A STUDY OF THE ORIGIN AND DEVELOPMENT OF A THEATRE CENTRE IN AN AFRICAN UNIVERSITY (1992)
The aim of this research is to highlight the historical significance of the contributions of the Arts Theatre, University of Ibadan, to theatre development in Nigeria. A remarkable landmark in theatrical development was reached in 1955 by the commissioning of the Arts Theatre - the first well-equipped modern theatre in Nigeria. It is significant because, hitherto, the professional theatre had been sneered at in Nigeria and had only flourished as a peripatetic vocation tenously sustained by the enthusiasm of Hubert Ogunde Dance Theatre Company and the nascent Yoruba travelling troupes. But today, theatre has become a household phenomenon, about which the Arts Theatre has disseminated positive information in the last three decades. The educational programmes incepted at the Arts Theatre in 1963 have matured into full university degree programme. The success of this initiative has further inspired the establishment of similar programmes in many other Nigerian Universities. Today, students take degrees in Theatre Arts and fill high level manpower positions in government and private enterprises after graduation. The Arts Theatre has also bred frontline playwrights, distinguished scholars and accomplished theatre practitioners. The Arts Theatre also remains the main source of inspiration for new theatre structures and resident university theatre troupes. This thesis examines fully the implications of the fact that the Arts Theatre was the first architectural archetype designed for the serious promotion of theatrical activities and which has made the theatre a respectable profession in Nigeria, We conclude that, though beset by old age, the Arts Theatre is capable of further active contributions if properly refurbished, maintained and efficiently administered. We set out by introducing our aims, our research methodology and definition of terms. Here also we identify our problem and define our scope of study. Chapter I contains a review of relevant literary works on reputable Arts Theatres in the world, the origin of theatre as academic subject and the structural attributes of the Arts Theatre. Chapter 2 traces the purpose of the university, origin and development of the Arts Theatre, theatre forms, the early dramatic activities of Randall Hogarth and various other contributions made by Geoffrey Axworthy, Wole Soyinka and Joel Adedeji. Chapter 3 focusses attention on systematic theatre education at Ibadan highlighting its workshop origin, evolution of academic programmes and associated amateur student and staff production; children's theatre, yoruba Travelling theatre and film. Chapter 4 deals with the promotion of theatre profession in Nigeria focusing on the implications of the University Acting Companies and promotion of African writings, International Productions and Foreign Visiting Artists and workshop. Chapter 5 contains a retrospective review of fields covered in the work and results achieved. It is also the concluding chapter. The Appendices and the plates have been carefully selected principally to provide objective insight into the various Arts Theatre activities. Interview with Professor Fola Aboaba for instance touches on a wide range of the Arts Theatre events.